СТРУКТУРНО-ФУНКЦІОНАЛЬНА МОДЕЛЬ ОБ’ЄДНАНОЇ ТЕРИТОРІАЛЬНОЇ ГРОМАДИ ЯК ПЕРВИННОГО ЕЛЕМЕНТА СИСТЕМИ МІСЦЕВОГО САМОВРЯДУВАННЯ (International Journal of Innovative Technologies in Economy, 2018)
In the article, based on the use of classical formulas describing the operation of a typical management couple of the "subject-object" covered by the feedback, in which the transformation coefficients of the pair of elements are interpreted as the ratio of the value of the product to the cost of resources spent on it, proposed to interpret the socio- Economic system of the united territorial community in the form of a structural and functional scheme of interaction of the governing body of the functioning of the system and a plurality of objects in its management - natural chnyh and entities, the results of which form a joint product of the local community. On the example of the structural-functional scheme of the system it was demonstrated that the results of its activities are formed with the participation of the coefficients of transformation of all its constituent elements, the state of direct and reciprocal relations between them, as well as the state of socio-cultural, existential and thoughtful communications between their human resources. It is also shown that in addition to formal communications and communications, informal connections and communications arise between individual elements of the system and create a virtual structural-functional scheme as a consequence of the lack of democratic governance, mutual understanding and trust between the elements of the system. The influence of the virtual structural-functional scheme on the general results of the functioning of the system is, as a rule, negative, which worsens the performance of the formalized structure. The requirements for managers and functionaries of the management body and the conditions for implementation of which the interaction of the subject of management and the plurality of objects of management in the system is grounded on the basis of a joint, open and transparent decision-making on the proper, efficient and effective use of community resources. The ways of further investigations of the complex interaction of formalized and virtual functional structures with the aim of minimizing the influence of the virtual structure of communications and, obviously, improvement of the results of the system by identifying opportunities and conditions for achieving the synergy effect for its successful functioning and development are determined.